PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH FISIKA DI KELAS XI IPA SMA N 2 TELUK KUANTAN - Sinaga, Ester SP Sinaga; Irianti, Mitiri Irianti; ', M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract:Thisresearchaimsto improve students' ability to solve problems in material physics kinematics with vector analysis in class XI IPA1 SMA N 2 TelukKuantan.The subjects were students of class XI IPA1 of 20 people consisting of 7 male students and 13 female students. Data collection instrument in this study is testing the ability of problem solving, observation of teacher performance, and questionnaire feasibility study model.Analysis of the data in this study is a descriptive analysis to see an increase in students' ability to solve physics problems with the indicator to understand the problem, solving plan, implement solutions, and conclude the breakdown.From the analysis of the data showed: the average percentage score on the problem solving ability of pre cycle of 25% with a very low skill level category, in the first cycle the average percentage score of 50.50% problem solving skills with the ability of very low-level category, and the second cycle the average score of 75.50% problem solving ability with moderate skill level category. Thus, it can be concluded that the application of problem-based learning learning model can improve the ability to solve problems in a class XI student of physics IPA1 MAN 2 TelukKuantan. KeyWords:problem based learning, ability of problem solving, kinematics